2020
DOI: 10.1038/s41598-020-72035-1
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of salivary microbiome in periodontitis with or without type-2 diabetes mellitus and metformin treatment

Abstract: We aimed to explore the effects of type-2 diabetes mellitus (T2DM) and hypoglycemic therapy on the salivary microbiome in periodontitis patients and identify the potential salivary micro-biomarker for the early warning of T2DM. Saliva samples were collected from healthy individuals (Health), periodontitis patients (P), T2DM patients, periodontitis patients with T2DM (DAP), and DAP patients treated with Metformin (Met). Samples were determined by16S rRNA gene sequencing. 29 phyla, 322 genera, and 333 species of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 38 publications
2
68
2
1
Order By: Relevance
“…In contrast, Saeb et al (2019) found the opposite trend when comparing the impaired glucose tolerance and diabetes group with the normoglycemic group [ 29 ]. Chao1 and Shannon’s diversity indices of oral microbiome in PPG FPG were higher than those in NG FPG , which is well in agreement with other studies of T2DM patients [ 40 , 41 , 42 ]. It is found that the oral microbiomes are potentially influenced by various factors such as oral health and host characteristics [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, Saeb et al (2019) found the opposite trend when comparing the impaired glucose tolerance and diabetes group with the normoglycemic group [ 29 ]. Chao1 and Shannon’s diversity indices of oral microbiome in PPG FPG were higher than those in NG FPG , which is well in agreement with other studies of T2DM patients [ 40 , 41 , 42 ]. It is found that the oral microbiomes are potentially influenced by various factors such as oral health and host characteristics [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, it may not reflect the actual result because phenotypic identification systems have insufficient databases for this microorganism. Alloprevotella rava has been detected in the oral microbiota of certain patients with oral dysbiosis by molecular techniques since 2013, when it was defined [ [2] , [3] , [4] ]. An epidemiological study, conducted among Chinese preschool children, revealed that the relative proportions of A. rava were significantly higher in the halitosis group compared with the control group [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort study showed a relationship between an increase in dental caries and the level of the genus Alloprevotella in the oral microbiome among Japanese university students [ 3 ]. Another report indicated that the proportion of A. rava was significantly increased in saliva samples of periodontitis patients [ 4 ]. On the other hand, Coit et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral cancer [31] Ralstonia Periodontitis [32] Sphingomonas Recurrent aphthous ulcer [33] Gram-positive Actinomyces Dental caries [34] Bacillus Dental caries [35] Corynebacterium Biofilm formation [36] Lactobacillus Dental caries [34]…”
Section: Gram Staining Genusmentioning
confidence: 99%